2004
DOI: 10.1002/pola.20466
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched fluoropolymer and linear poly(ethylene glycol) based amphiphilic crosslinked networks as efficient antifouling coatings: An insight into the surface compositions, topographies, and morphologies

Abstract: Polymer coatings with features of differing hydrophilicity, mobility, and topography, distributed across a substrate in microscopic and nanoscopic patches were designed as complex materials equipped with sufficient variability in composition, structure, and dynamics to inhibit interactions associated with biomacromolecular fouling. These complex polymer coatings were prepared by the in situ phase separation and crosslinking of mixtures of hyperbranched fluoropolymer (HBFP) and diamino‐terminated poly(ethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
199
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(206 citation statements)
references
References 79 publications
(91 reference statements)
6
199
1
Order By: Relevance
“…Along this line, Gudipati et al (2004Gudipati et al ( , 2005 prepared amphiphilic polymer networks containing hyperbranched fluoropolymers crosslinked with PEG, in which phase segregation resulted in a higher release of Ulva sporelings (young plants) compared to PDMS. More recently the present authors reported on the preparation of SEBS-based coatings containing a polystyrene-based diblock copolymer carrying PEGylated-fluoroalkyl side chains capable of reducing the adhesion of both Ulva sporelings and cells of the diatom Navicula (Martinelli et al 2008).…”
mentioning
confidence: 99%
“…Along this line, Gudipati et al (2004Gudipati et al ( , 2005 prepared amphiphilic polymer networks containing hyperbranched fluoropolymers crosslinked with PEG, in which phase segregation resulted in a higher release of Ulva sporelings (young plants) compared to PDMS. More recently the present authors reported on the preparation of SEBS-based coatings containing a polystyrene-based diblock copolymer carrying PEGylated-fluoroalkyl side chains capable of reducing the adhesion of both Ulva sporelings and cells of the diatom Navicula (Martinelli et al 2008).…”
mentioning
confidence: 99%
“…This combination of functionality and architecture lend the dendrimers toward use as cross-linkers by a process that is similar to that demonstrated for other dendrimers 77,78 and hyperbranched polymers. 79,80 Investigations of the applications of these Click-constructed dendrimers as reactive and multifunctional globular macromolecules are underway. …”
Section: Discussionmentioning
confidence: 99%
“…12 Research has demonstrated that two different algal species, one of which adhered strongly to hydrophobic surfaces, and the other, to hydrophilic surfaces, showed notably weak adhesion to the amphiphilic polymer surfaces. 12 Pioneer research in such binary systems comes from the work of Wooley and coworkers, [13][14][15] who reported amphiphilic polymer coatings prepared by the in situ phase separation and crosslinking of hyperbranched fluoropolymers and linear PEG networks for efficient antifouling coatings. Since then, surface-active block copolymers with fluoroalkyl side chains, amphiphilic semifluorinated block copolymers have been explored in antifouling coatings.…”
mentioning
confidence: 98%